PENGARUH PENGGUNAAN TIKTOK SHOP TERHADAP SIKAP PEMBELIAN IMPULSIF (STUDI EKSPLANASI PEMBELIAN IMPULSIF PADA PRODUK SOMETHINC DI TIKTOK SHOP OLEH MAHASISIWI DKI JAKARTA) - Celica Zalfa Arvioby (2023)
This research is motivated by the existence of impulsive buying attitudes in female students because it has the greatest influence on the emotional aspects of making purchases both offline and online. The TikTok Shop phenomenon as a selling feature can be researched on its use by female students in DKI Jakarta on the local beauty brand "Somethinc". The purpose of this study was to determine the significant effect of TikTok Shop on the local brand Somethinc on impulsive buying attitudes with female students in DKI Jakarta as the subject. The supporting theory of this research is Information Seeking Behavior regarding information seeking. This study uses a quantitative method of cluster sampling technique with random sampling technique in the form of a Google Form questionnaire with 100 respondents. The results of this study are that there is a significant influence between the use of TikTok Shop on impulsive buying attitudes of 47.8%. There is an influence between the use of TikTok Shop as a social media Brand Somethinc on the impulsive buying attitudes of female students in both cognitive and affective aspects in DKI Jakarta.